PELAKSANAAN PROGRAM LITERASI, NUMERASI DAN ADAPTASI TEKNOLOGI INFORMASI DAN ADMINISTRASI KAMPUS MENGAJAR ANGKATAN 4 DI SMP MUHAMMADIYAH 57 MEDAN - Elisabeth, Duma Megaria; Hasanah, Nurul; Maharani, Nurul Latiefah; Sapitri, Nurul; Manalu, Offiani; Br. Ginting, Paschloudya (Universitas Methodist Indonesia, 2023)
The Independent Campus Learning Program (MBKM) is one of the programs organized by the Ministry of Education and Culture. The Teaching Campus Program is one of the programs in the Merdeka Learning Campus Program which has the aim of teaching, as well as increasing numeracy literacy, assisting technology, and assisting school administration and teachers in target schools. One of the schools that became the target of the Teaching Campus Batch 4 program was SMP Muhammadiyah 57 Medan, which is located on Jl. Mustafa, Glugur Darat I District, East Medan District, North Sumatra Province. In the Teaching Campus program, students who are appointed to take part in the program have the responsibility of assisting the school in the teaching process, assisting with adaptation to technology, and assisting with school administration. In addition, Teaching Campus students have the responsibility to improve student character and increase student interest in learning after this pandemic. The purpose of student participation in the Teaching Campus program is a process of adding relationships, adding experience outside the world of lectures, developing students' insights, character and soft skills, encouraging and spurring national development by fostering student motivation to participate in development, as well as increasing the role and the real contribution of universities and students in the development of education in Indonesia.